Prevalence of Noonan spectrum disorders in a pediatric population with valvar pulmonary stenosis. (16th December 2018) - Anderson, Kailyn; Cnota, James; James, Jeanne; Miller, Erin M.; Parrott, Ashley; Pilipenko, Valentina; Weaver, Kathryn Nicole; Shikany, Amy
Abstract: Objective: To evaluate the prevalence of Noonan spectrum disorders (NSD) in a pediatric population with valvar pulmonary stenosis (vPS) and identify the clinical characteristics that differentiate those with NSD from those without NSD. Design: A retrospective chart review of 204 patients diagnosed with vPS between 9/1/2012 and 12/1/2016 at a pediatric medical center was performed. The quantitative features of vPS, genetic diagnosis information, and phenotypic characteristics of Noonan syndrome were collected. Chi‐square test, Fisher's exact test, t test, Wilcoxon rank‐sum test, andANOVA were used for comparisons among the groups. Logistic regression was used to test for the association between the clinical characteristics and the presence of NSD. Results: Syndromic diagnoses were made in 10% of the children with vPS, with NSD accounting for 6%. Hypertrophic cardiomyopathy ( P  < .0001), short stature ( P  < .0001), developmental delay ( P  < .0001), ophthalmological abnormalities ( P  < .0001), pectus carinatum/excavatum ( P  = .01), neurological abnormalities ( P  = .022), and aortic stenosis ( P  = .031) were present more often in individuals with NSD compared to nonsyndromic vPS. A logistic regression analysis showed a 4.8‐fold increase in odds for NSD for each additional characteristic ( P  < .0001). Conclusions: At least 6% of the children with vPS have an underlying NSD. Individuals with vPS and NSD were significantly more likely to have additional features known to be associated with NSD than those with vPS without NSD. We conclude that vPS in the presence of one or more significant characteristics should prompt referral for genetic evaluation as a guide to ascertain patients at risk for NSD while optimizing the use of clinical genetics evaluation and potential genetic testing.